PENGARUH REWARD AND PUNISHMENT TERHADAP DISIPLIN SISWA KELAS 2 SD - Naffa Asti Aprilia; Agiskan Cahnia; Ayyatullah Muhammadin Al Fath; Erwin Efendi Hutagalung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the limited number of studies that comprehensively examine the implementation of reward and punishment in improving elementary school students’ discipline, despite its significant impact on the quality of the learning process and character development. The purpose of this study is to analyze the effect of reward and punishment on student discipline and to examine the effectiveness of these strategies in shaping disciplined behavior. This study adopts a qualitative approach using a library research design, with data sources derived from various scholarly literatures selected through purposive sampling. Data were collected through documentation techniques and analyzed using descriptive qualitative analysis. The findings indicate that rewards have a positive influence on enhancing students’ motivation and discipline, while appropriately implemented punishment can reduce violations and improve compliance with rules. These findings are consistent with reinforcement theory, which highlights the role of external stimuli in shaping behavior. The study concludes that the combination of reward and punishment is an effective strategy for improving student discipline in elementary schools. The implications of this study include theoretical contributions to the literature on character education strategies and practical recommendations for teachers to apply a balanced approach in classroom management. This study also suggests the need for further empirical research to examine the effectiveness of these strategies in real classroom settings.